GE_GERICHTE P/27638/2023 vom 10. Januar 2024 - GE Cour de justice (2024)
RÉSERVE DE PROPRIÉTÉ;VOL(DROIT PÉNAL);APPROPRIATION ILLÉGITIME;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE | CPP.310.al1.leta; CPP.393; CP.137; CP.139